A Comprehensive Study of Egyptian Arabic. Volume Two Proverbs and Metaphoric Expressions - Abdel-Massih, Ernest T.; Michigan Univ., Ann Arbor. Center for Near Eastern and North African Studies ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1978)
This is the second of four instructional volumes designed for the intermediate-advanced student of Egyptian Arabic. The course deals with the language, culture, customs, and traditions of Egypt. The present volume acquaints the American student with the important roles proverbs and metaphoric expressions play in everyday speech in Egyptian Arabic. Following a general discussion of proverbs and metaphoric expressions used in Egypt, specific proverbs are set forth, transliterated, and translated for 30 different categories of cultural life. Several hundred metaphors are then listed, literally translated, explained in a few English words, and used in a sentence, which is also translated. (JB)
Availability: Center for Near Eastern and North African Studies, 144 Lane Hall, The University of Michigan, Ann Arbor, MI 48109; Accompanying tapes from the University of Michigan Audiovisual Education Center, Tape Duplication Service, 416 S. Fourth Street, Ann Arbor, MI 48109.
Sponsoring Agency: Bureau of Postsecondary Education (DHEW/OE), Washington, DC. Div. of International Education.
Contract Number: 300-75-0302.
ERIC Note: For related documents, see FL 011 651-654.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Arabic; Area Studies; Cultural Education; Higher Education; Metaphors; Proverbs; Second Language Instruction; Egypt; Arabic (Egyptian) -- National Defense Education Act Title VI; Guides, Classroom -- Learner; Reference Materials, General